2008
DOI: 10.4028/www.scientific.net/amr.55-57.61
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Conducting Polymer Films by Plasma Polymerization Process

Abstract: A microwave (MW) plasma reactor for the synthesis of polythiophene (PTh) thin films as well as in situ doping during polymerization process has been designed and assembled. Plasma polymerization parameters were studied. A good MW power was found to be in the range of 150-250W. PTh films were characterized by various spectrophotometric methods. IR analyses showed absorption frequencies of important functional groups. PTh films exhibited UV-Vis spectra indicative of increased conjugative systems as the MW power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…This may be ascribed to differences in bond energies among C-C, C=C, and C-N (348, 614, and 305 kJ mol −1 , respectively). It has been proposed that an increase in the number of collisions between electrons and other plasma species may have caused the relatively weaker C-N bond to break at a little higher extent, hence some loss of N from film composition as similarly seen in the case of plasma-polymerized thiophene (with C-S bond energy of 248 kJ mol −1 ) [25,26]. Also this is consistent with the findings of Hosono [13,16,17].…”
Section: Characterization Of Plasma-polymerized Polypyrrole (Ppppy) Fsupporting
confidence: 79%
“…This may be ascribed to differences in bond energies among C-C, C=C, and C-N (348, 614, and 305 kJ mol −1 , respectively). It has been proposed that an increase in the number of collisions between electrons and other plasma species may have caused the relatively weaker C-N bond to break at a little higher extent, hence some loss of N from film composition as similarly seen in the case of plasma-polymerized thiophene (with C-S bond energy of 248 kJ mol −1 ) [25,26]. Also this is consistent with the findings of Hosono [13,16,17].…”
Section: Characterization Of Plasma-polymerized Polypyrrole (Ppppy) Fsupporting
confidence: 79%
“…Moreover, it has been suggested that an enhancement in the number of between electrons and other plasma species that allow it to have loss of N from fabric [33]. The above results are consistent with previous literature [45,46]. The same situation was formed after doping process.…”
Section: Sem and Eds Resultssupporting
confidence: 94%
“…Surface & Coatings Technology j o u r n a l h o m e p a g e : w w w. e l s ev i e r. c o m / l o c a t e / s u r fc o a t described [17]. Microwave can be fed into the middle reactor chamber via the air-filled aluminum rectangular waveguide which is designed based on the WR340 standard; with internal cross section dimensions of 86.4 mm by 43.2 mm.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Many polyheterocyclic aromatic compounds having good thermal stabilities and high electrical conductivities could also be added to the list of organic conducting polymers. Polythiophene (PTh) [6] is one of the polyheterocyclics widely studied and plasma polymerization methods have also been utilized for their synthesis to alleviate problems associated with insolubility of PTh in most organic solvents [7][8][9][10][11][12][13][14][15][16][17] which usually result in difficulties in the processing stage. PTh exhibits high electrical conductivity upon doping, therefore, potential applications exist in many areas including sensors, organic light emitting diodes, solar cells, applications requiring photonic and conductive properties and polymeric batteries.…”
Section: Introductionmentioning
confidence: 99%